CEO Hakim's SCC Soft Computer stays ahead of the curve. - Hakim G (Medical Laboratory Observer (MLO), 2004)
As it celebrates its 25th year, SCC shares the same goals as its laboratory customers: increased productivity distribution, and a higher level of patient care.